Morphological, biochemical and molecular hallmarks of programmed cell death in stigmatic papillae of Brassica oleracea L. - ÇETİNBAŞ GENÇ, ASLIHAN; VARDAR, FİLİZ (FIRENZE UNIV PRESS, 2021)
The aim of this study is to determine the programmed cell death hallmarks in the stigmatic papillae of Brassica oleracea L. The flower development was divided in two main stages; pre-anthesis and post-anthesis. Programmed cell death hallmarks were examined in parallel to these stages. At pre-anthesis, the stigmatic papillae were ovoid and their dense cytoplasm were rich in insoluble polysaccharide and protein. At post-anthesis, vacuolization and enlargement were quite evident in papillae. Besides, the protein content decreased, but reactive oxygen species increased in comparison to the pre-anthesis stage. Although no significant change in superoxide dismutase activity was detected, catalase activity decreased and hydrogen peroxide content increased at post-anthesis. DAPI stained nuclei appeared rounded and smooth appearance at pre-anthesis, however, some invaginations and fragmentation in nuclei were observed at post-anthesis. Although, TUNEL staining was negative at pre-anthesis, while TUNEL positive reaction was significant in the nuclei of papillae at post-anthesis. In comparison to the pre-anthesis, the number of fragmented nuclei monitored by DAPI and TUNEL staining increased at post-anthesis.
Keywords: programmed cell death; papillae; reactive oxygen species; sexual plant reproduction; TUNEL; OXIDATIVE STRESS; NITRIC-OXIDE; POLLEN; SENESCENCE; DEGENERATION; DEGRADATION; RECEPTIVITY; APOPTOSIS; EVENTS; MAIZE